Risk factors for stillbirth at term: an Italian area-based, prospective cohort studyAJOG Global Reports at a Glance - Cristina Salerno, MD; Beatrice Melis, MD; Valeria Donno, MD; Gloria Guariglia, MD; Daniela Menichini; Enrica Perrone, MD; Fabio Facchinetti, MD; Francesca Monari, MD (Elsevier, 2023)
BACKGROUND: Stillbirth at term has great emotional impact on both parents and professionals. In developed countries, efforts to identify risk factors are mandatory to plan area-specific prevention strategies. OBJECTIVE: The aim of the study was to identify independent risk factors that contribute to stillbirth at 37 weeks' gestation or later. STUDY DESIGN: This was an area-based, prospective cohort study on pregnancy at term with enrolled from 2014 to 2021 in Emilia-Romagna, a north Italian region. Data were retrieved from both birth certificates and the Stillbirth Surveillance system database. To identify independent risk factors, a multivariate analysis using logistic regression was performed. A descriptive analysis of the causes of stillbirth is also reported. RESULTS: In the observation period, 246,437 babies born at term (including 260 stillbirths, giving a rate of 1.06/1000) were considered. The risk factors independently associated with stillbirth were small for gestational age babies (odds ratio, 2.58; 95% confidence interval, 1.88-3.53), pregnancy achieved though fertility treatments (odds ratio, 2.01; 95% confidence interval, 1.15-3.51), and delayed access to pregnancy services (odds ratio, 1.56; 95% confidence interval, 1.10-2.22). In multipara, the presence of a previous stillbirth (odds ratio, 3.91; 95% confidence interval, 1.98-7.72) was also associated with an increased risk for recurrence. Early- rather than late-term was an additional risk factor. The most frequent causes of death were placental and cord disorders (61/260 and 56/260, respectively). However, 28.1% of cases remain unexplained. CONCLUSION: The risks for stillbirth at term are known early in pregnancy or could be identified through tailored antenatal management, allowing effective preventive strategies to reduce preventable cases.